2013
DOI: 10.4103/1319-3767.121035
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Hepatitis B surface antigen titers and HBV DNA levels

Abstract: Background/Aim:To assess the correlation between serum HBsAg titers and hepatitis B virus (HBV) DNA levels in patients with hepatitis B envelop antigen-negative (HBeAg −ve) HBV genotype-D (HBV/D) infection.Patients and Methods:A total of 106 treatment- naïve, HBeAg −ve HBV/D patients were included; 78 in the inactive carrier (IC) state and 28 in the active hepatitis (AH) stage. HBV DNA load and HBsAg titers were tested using TaqMan real-time polymerase chain reaction (PCR) and automated chemiluminescent microp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 29 publications
(32 reference statements)
0
24
0
Order By: Relevance
“…[ 15 – 17 ] However, HBeAg is still qualitatively assayed despite advances in quantitative detection of HBsAg. [ 18 ] Furthermore, a truly quantitative relationship between HBeAg and HBV DNA levels remains to be established. In this study, we conducted a large-scale community-based screening of HBV-infected individuals by random collection of blood samples from the entire populations of 12 villages.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 – 17 ] However, HBeAg is still qualitatively assayed despite advances in quantitative detection of HBsAg. [ 18 ] Furthermore, a truly quantitative relationship between HBeAg and HBV DNA levels remains to be established. In this study, we conducted a large-scale community-based screening of HBV-infected individuals by random collection of blood samples from the entire populations of 12 villages.…”
Section: Introductionmentioning
confidence: 99%
“…The level of HBeAg was evaluated using the S/CO, and HBeAg positivity was confirmed in those with an S/CO ≥1.0. [ 36 ] A sub-analysis showed that patients who received consolidation therapy for 18 months and had a baseline level of HBeAg >1000 S/CO experienced a significantly lower risk of relapse. In other words, a prolonged consolidation period was beneficial to patients with a high baseline semi-quantitative level of HBeAg in terms of off-treatment durability.…”
Section: Discussionmentioning
confidence: 99%
“…Relative to other parts of the world, the prevalence of HBV in Iran varies from low to intermediate based on geographic region. Although there are an estimated 1.5 million chronically infected individuals ( 5 ), the rate of liver cancer is lower than might be expected, perhaps explained by a higher prevalence of genotype D, and high prevalence of HBeAg seronegativity or because of some mutations in core or pre-core region of the virus ( 10 , 11 ). On the other hand, HBV positive individuals in Middle Eastern countries have been shown to have a high susceptibility for acquisition of pre-core or basal core promoter variants that may affect HBeAg ( 10 ), but perhaps not HBV replication or other aspects of HBV.…”
Section: Introductionmentioning
confidence: 99%